Aberrant Structural and Functional Developmental Trajectories in Children With Intellectual Disability - Ma, Xuejin; Tan, Jianxia; Jiang, Lin; Wang, Xuqin; Cheng, Bochao; Xie, Peng; Li, Yuanyuan; Wang, Jiaojian; Li, Shiguang (Frontiers in Psychiatry, 2021)
Intellectual disability (ID) is associated with aberrant structural and functional development of brain, yet how the dynamical developmental changes of structure and function of ID from childhood to around puberty remains unknown. To explore the abnormal developmental trajectories of structure and function, 40 children with ID aged 6-13 years and 30 sex-, age-, and educational level-matched healthy controls (HC) with age range from 6-13 were recruited. The automatic voxel-based morphometry (VBM) and resting-state functional connectivity (FC) analyses were adopted to delineate the structural and functional differences. Significantly decreased total gray matter volume (GMV) and white matter volume (WMV) in children with ID were found, and the developmental trajectories of GMV and WMV in children with ID showed opposite direction as compared with HC. The voxel-wise VMB analysis further revealed significantly increased GMV in the dorsal medial prefrontal cortex (dmPFC), bilateral orbital part of the inferior frontal gyrus (orb_IFG.L, orb_IFG.R), right cuneus (cuneus.R), bilateral middle frontal gyrus (MFG.L, MFG.R) in children with ID. The following seed-based whole brain functional connectivity analyses of the brain areas with changed GMV found decreased FCs between the cuneus.R and left intraparietal sulcus (IPS.L), and between the MFG.R and anterior cingulate cortex (ACC) in children with ID. Moreover, negative correlations between GMV values in the dmPFC, orb_IFG.L, cuneus.R and intelligence quotient (IQ) scores, and positive correlations between the FCs of the cuneus.R with IPS.L and MFG.R with ACC and IQ scores were found in children with ID and HC. Our findings provide evidence for the abnormal structural and functional development in children with ID and highlight the important role of fronto-parietal network in the typical development. The abnormal development of GMV and functional couplings found in this study may be the neuropathological bases of children with ID.